Haemodynamic influences on kidney oxygenation: Clinical implications of integrative physiology. (29th January 2013) - Evans, Roger G; Ince, Can; Joles, Jaap A; Smith, David W; May, Clive N; O'Connor, Paul M; Gardiner, Bruce S
Summary Renal blood flow, local tissue perfusion and blood oxygen content are the major determinants of oxygen delivery to kidney tissue. Arterial pressure and segmental vascular resistance influence kidney oxygen consumption through effects on glomerular filtration rate and sodium reabsorption. Diffusive shunting of oxygen from arteries to veins in the cortex and from descending to ascending vasa recta in the medulla limits oxygen delivery to renal tissue. Oxygen shunting depends on the vascular network, renal haemodynamics and kidney oxygen consumption. Consequently, the impact of changes in renal haemodynamics on tissue oxygenation cannot necessarily be predicted intuitively and, instead, requires the integrative approach offered by computational modelling and multiple measuring modalities. Tissue hypoxia is a hallmark of acute kidney injury (AKI) arising from multiple initiating insults, including ischaemia–reperfusion injury, radiocontrast administration, cardiopulmonary bypass surgery, shock and sepsis. Its pathophysiology is defined by inflammation and/or ischaemia resulting in alterations in renal tissue oxygenation, nitric oxide bioavailability and oxygen radical homeostasis. This sequence of events appears to cause renal microcirculatory dysfunction, which may then be exacerbated by the inappropriate use of therapies common in peri‐operative medicine, such as fluid resuscitation. The development of new ways to prevent and treat AKI requires an integrative approach that considers not just the molecular mechanisms underlying failure of filtration and tissue damage, but also the contribution of haemodynamic factors that determine kidney oxygenation. The development of bedside monitors allowing continuous surveillance of renal haemodynamics, oxygenation and function should facilitate better prevention, detection and treatment of AKI.